A Theory-Informed Conceptual Framework for Sustainable Intangible Cultural Heritage Preservation in the Digital Era through Immersive Information Systems - Perwitasari, Ika Devi; Ariffin, Shamsul Arrieya; Jodi Hendrawan (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
The preservation of Intangible Cultural Heritage (ICH) faces significant challenges in the digital age, particularly regarding authentic representation, technology acceptance, and sustainability. This research aims to develop a theory-informed conceptual framework to support ICH preservation through immersive information systems. The approach used was conceptual, with a systematic literature review, theory synthesis, and framework development. The literature analyzed included cultural preservation theory, the Technology Acceptance Model (TAM), the User-Centered Design (UCD) approach, and the Culturally Appropriate Design Guidelines (CADG). The research results produced a framework consisting of three main dimensions: Cultural Appropriateness, Technological Acceptance, and Sustainability. These three dimensions lead to the development of Immersive Information Systems that incorporate VR, AR, and AI technologies as key enablers for the documentation, dissemination, and intergenerational transfer of cultural knowledge. The literature synthesis indicates that community engagement, user acceptance of technology, and social, technological, and economic sustainability strategies are key pillars of ICH preservation in the digital age. As an illustration, the case of the Toba Batak demonstrates how immersive technology can be used to document local cultural practices such as tortor, gondang sabangunan, and ulos. The study's conclusions emphasize that ICH preservation cannot be separated from the integration of preservation theory, technology adoption, and sustainable design. The resulting framework provides both theoretical contributions by broadening the horizons of cultural preservation studies and practical contributions as a guide for the ethical, inclusive, and sustainable implementation of immersive technology.